Merancang Dan Menganalisis Pelajaran Berbasis Tahap Perkembangan Kognitif Piaget Pada Kelas Sosilogi - A. Ratnawati; Suardi (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to design and analyze sociology learning based on Jean Piaget’s cognitive development stages. The research employed a qualitative approach with a descriptive qualitative design. The research subjects consisted of a sociology teacher and students from one class at the Madrasah Tsanawiyah level. Data were collected through interviews, observations, questionnaires, and documentation studies. The results indicate that sociology learning designed according to students’ cognitive development stages enhances student engagement, facilitates understanding of abstract sociological concepts, and promotes the development of critical and analytical thinking skills. Learning activities such as group discussions, case studies, and social simulations were found to effectively support students’ processes of assimilation and accommodation. Therefore, the implementation of Piaget’s cognitive development theory in sociology learning is relevant and effective in improving the quality of classroom learning. AbstrakPenelitian ini bertujuan untuk merancang dan menganalisis pembelajaran sosiologi yang berbasis pada tahap perkembangan kognitif Jean Piaget. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif kualitatif. Subjek penelitian terdiri atas seorang guru sosiologi dan siswa satu kelas pada jenjang Madrasah Tsanawiyah. Teknik pengumpulan data meliputi wawancara, observasi, angket, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa pembelajaran sosiologi yang disesuaikan dengan tahap perkembangan kognitif siswa mampu meningkatkan keterlibatan aktif siswa, mempermudah pemahaman konsep-konsep abstrak, serta mendorong berkembangnya kemampuan berpikir kritis dan analitis. Pembelajaran berbasis diskusi, studi kasus, dan simulasi sosial terbukti efektif dalam mendukung proses asimilasi dan akomodasi siswa. Dengan demikian, penerapan teori perkembangan kognitif Piaget dalam pembelajaran sosiologi relevan dan efektif untuk meningkatkan kualitas proses pembelajaran di kelas.